Retrieval practice protects memory against acute stress. - Smith, Amy M.; Floerke, Victoria A.; Thomas, Ayanna K. (Tufts University. Tisch Library., 2016)
More than a decade of research has supported a robust consensus: Acute stress impairs memory retrieval. We aimed to determine whether a highly effective learning technique could strengthen memory against the negative effects of stress. To bolster memory, we used retrieval practice, or the act of taking practice tests. Participants first learned stimuli by either restudying or engaging in retrieval practice. Twenty-four hours later, we induced stress in half of the participants and assessed subsequent memory performance. Participants who learned by restudying demonstrated the typical stress-related memory impairment, whereas those who learned by retrieval practice were immune to the deleterious effects of stress. These results suggest that the effects of stress on memory retrieval may be contingent on the strength of the memory representations themselves.